2019
DOI: 10.1177/0734242x19877677
|View full text |Cite
|
Sign up to set email alerts
|

Economic and environmental consequences of implementing an EU model for collecting and separating wastes system in Lebanon

Abstract: In this study, we examine the economic and environmental significance associated with the implementation of an EU waste-separated collection scheme in a developing context – Lebanon. Two scenarios, S1 and S2, representing different intensities of source segregation were analysed. In S1, the average source segregation intensity reached 25% and 13% for the Italian test area and Lebanese test area, respectively. In S2, source segregation intensity increased to 48% and 68% for the Italian and Lebanese test areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The challenges associated with MSW management during the pandemic mainly include the following: (a) increased amount of mixed waste including infectious waste as there is no waste segregation at source; (b) increased littering, open burning and illegal dumping of MSW, including infectious COVID-19-related waste, which are still commonly practised in many areas; (c) increased negative impacts from potential exposures to informal workers in contact with waste mixed with infectious waste such as gloves, masks and tissues; and (d) lack of daily supply of PPE to waste collectors and awareness regarding waste handling, which caused in July 2020 the coronavirus infection of 133 workers from a waste management company in Lebanon as reported by the Ministry of Public Health (Reuters, 2020). It should be noted that in Lebanon estimates on amount of household infectious waste being generated related to COVID-19 is lacking as there is no MSW separation at source (Maalouf et al, 2019). Therefore, the estimated amount of COVID-19-related waste reported in this study is only associated with waste generated through healthcare facilities and not through households.…”
Section: Resultsmentioning
confidence: 99%
“…The challenges associated with MSW management during the pandemic mainly include the following: (a) increased amount of mixed waste including infectious waste as there is no waste segregation at source; (b) increased littering, open burning and illegal dumping of MSW, including infectious COVID-19-related waste, which are still commonly practised in many areas; (c) increased negative impacts from potential exposures to informal workers in contact with waste mixed with infectious waste such as gloves, masks and tissues; and (d) lack of daily supply of PPE to waste collectors and awareness regarding waste handling, which caused in July 2020 the coronavirus infection of 133 workers from a waste management company in Lebanon as reported by the Ministry of Public Health (Reuters, 2020). It should be noted that in Lebanon estimates on amount of household infectious waste being generated related to COVID-19 is lacking as there is no MSW separation at source (Maalouf et al, 2019). Therefore, the estimated amount of COVID-19-related waste reported in this study is only associated with waste generated through healthcare facilities and not through households.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the methodological and scientific correctness, these studies reported quite different results mainly due to the different contexts (e.g., energy mix, resource consumed, technologies adopted in the industrial process and pollution control systems) in which they were implemented and the different assumptions made. These differences can be noted in the amount of kgCO 2eq avoided up to −370 kgCO 2eq /tonne waste [8,9] and/or emitted, up to 900 kgCO 2eq /tonne waste [11], and in the amount of CFC-11eq and SO 2eq avoided. These findings indicate that the context in which the same process, system and/or technology is implemented can influence the calculation of the net amounts of emissions and/or materials consumed, leading to opposite results.…”
Section: Introductionmentioning
confidence: 95%
“…One of the most diffused approaches for evaluating environmental impact is the life cycle assessment (LCA) that is largely exploited in the WM sector as demonstrated by several studies in this field, e.g., Di Maria and Micale [8] for the Italian and Maalouf et al [9] for the Lebanese contexts. Similarly, other studies adopting LCA for assessing the environmental impact of MW are those of Yay [10] for the Turkish, Bovea et al [11] for the Spanish and Weitz et al [12] for the USA contexts.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies (Maalouf and El-Fadel, 2018b, 2019) showed that substituting open dumping or burning with proper waste management systems such as engineered landfills coupled with a proper landfill gas collection system, incineration, recycling, biological treatment, food waste diversion, and/or energy recovery can contribute to significant savings in emissions that can reach up to 24–95% compared to the baseline, depending on the tested system. Another study by Maalouf et al (2019) reported that the increase in the source segregation intensity with proper management of residual MSW resulted in significant savings in the climate change impact (reaching up to 20%) and stratospheric ozone depletion potential (about 55%) in a developing economy. As such, the delivery of infrastructure for MSW is driven by increased concerted policy action in an effort to reduce or eliminate uncontrolled waste disposal practices, especially in the developing world.…”
Section: Introductionmentioning
confidence: 99%